Influence of Carbohydrates on Callus Proliferation During Somatic Embryogenesis in Pineapple [Ananas Comosus (L.) Merr. (Bromeliaceae) Var. Cayenne Smooth Cultivar CI 16] - Samuel, Kouadio Oi Kouadio; SalomÃ©, Yapo Edwige Sopie; Oumar, Silue; Christophe, Adou Bini Yao; Hilaire, Kouakou Tanoh (European Scientific Journal, ESJ, 2018)
The improvement of pineapple (Ananas comosus var. Smooth Cayenne) by means of in vitro culture is less studied in CÃ´te d’Ivoire despite the importance of this plant for this countryâ€™s economy. Our work consisted in highlighting nature and concentration effects of carbohydrates on the proliferation of calli in pineapple as a prelude to efficient embryogenesis. Callus proliferation was carried out from the base of pineapple vitroplants leaves. Thirty (30) explants were cultured on the tested culture medium. MS medium (micro- and macro elements of Murashige and Skoog) supplemented with vitamin Gamborg B5 was used as base medium to which were added 0.05 mg/L BAP, 3 mg/L picloram, 2 mg/L glycine, 1,000 mg/L glutamine, 100 mg/L casein hydrolyzate and 30 g/L carbohydrate. Sucrose was tested at different concentrations (20, 25, 30, 35 and 40 g/L). The results revealed that callus proliferation is strongly influenced (p Ë‚ 0.0001) by nature and concentration of carbohydrate. Sucrose with the highest dry matter content (61.34 mg) has a higher callogenic potential than the other studied carbohydrates. The concentration of 30 g/L sucrose significantly improved the calli proliferation in pineapple. Galactose and maltose were less favorable to proliferation.